THE ROLE OF THE BOARD OF COMMISSIONERS IN IMPROVING THE QUALITY OF FINANCIAL REPORTS: THE INFLUENCE OF AGE, EXPERIENCE AND EDUCATION ON TRADE, SERVICES AND INVESTMENT COMPANIES - Ferry Safriandi; Aria Masdiana Pasaribu; Windy Aginta (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of age, experience, and education of board commissioners on the quality of financial reports in companies in the trading, service, and investment sectors listed on the Indonesia Stock Exchange (IDX). The method used in this study is descriptive quantitative. The population of this study are companies in the trading, service, and investment sectors listed on the IDX. The sample size is 49. The analysis technique used is multiple linear regression The results of this study are the t-count value I is greater than the t-table value (-0.117 smaller than I 2.028) and the significant value of 0.907 I is greater than 0.05 I indicates that age partially has no effect on the quality of financial reports. The t-count value I is greater than the t-table value (-0.570 smaller than I 2.028) and the significant value of 0.570 I is greater than 0.05 I indicates that experience partially has no effect on the quality of financial reports. The t-count value I is greater than the t-table value (-0.874 smaller than I 2.028) and the significant value of 0.385 greater than 0.05 I indicates that education has partially no effect on the quality of financial reports. According to Table 3, the calculated F value for each variable (age, experience, and education of the board of commissioners) is 0.408, with a significance level of 0.748, which is greater than 0.05. Therefore, it can be concluded that each independent variable (age, experience, and education of the board of commissioners) simultaneously has no effect on the dependent variable (financial reporting quality).